The Thin White Line: Adaptation Suggests a Common Neural Mechanism for Judgments of Asian and Caucasian Body Size - Gould-Fensom, Lewis; Tan, Chrystalle B. Y.; Brooks, Kevin R.; Mond, Jonathan; Stevenson, Richard J.; Stephen, Ian D. (Frontiers in Psychology, 2019)
Visual adaptation has been proposed as a mechanism linking viewing images of thin women’s bodies with body size and shape misperception (BSSM). Non-Caucasian populations appear less susceptible to BSSM, possibly because adaptation to thin Caucasian bodies in Western media may not fully transfer to own-race bodies. Experiment 1 used a cross-adaptation paradigm to examine the transfer of body size aftereffects across races. Large aftereffects were found in the predicted directions for all conditions. The strength of aftereffects was statistically equivalent when the race of test stimuli was congruent vs incongruent with the race of adaptation stimuli, suggesting complete transfer of aftereffects across races. Experiment 2 used a contingent-adaptation paradigm, finding that simultaneous adaptation to wide Asian and narrow Caucasian women’s bodies (or vice versa) results in no significant aftereffects for either congruent or incongruent conditions, and statistically equivalent results for each. Equal and opposite adaptation effects may therefore transfer completely across races, cancelling each other out. This suggests that body size is encoded by a race-general neural mechanism. Unexpectedly, Asian observers showed reduced body size aftereffects compared to Caucasian observers, regardless of the race of stimulus bodies, perhaps helping to explain why Asian populations appear less susceptible to BSSM.